Competencias digitales docentes y la práctica pedagógica en Matemática del Subnivel Elemental, Escuela de Educación Básica Municipal La Pradera, Loja 2024 - Yaguana Valverde, Silvana Alexandra (2024)
The purpose of the degree work presented below is to analyze the digital competencies of teachers and their impact on the pedagogical practice in the teaching of mathematics in the elementary sublevel of the municipal basic education school la pradera in Loja. The research is based on the development, use and application of digital competencies by teachers, aspects that are essential to improve educational quality and prepare students to face the challenges of the 21st century. Therefore, the study employed a qualitative approach methodology, descriptive type and quasi-experimental design, to collect detailed data on teachers' digital competencies and their application in the classroom. The results obtained significantly revealed the variable level of skills in digital competencies possessed by teachers, which directly impacts the quality of teaching. Through the identification of these deficiencies, the urgent need for continuous education and training in the use of technological tools that can enrich the pedagogical practice was evidenced. In addition, it was found that the technological resources in the institution are not adequate and the lack of them limit this digital integration. The conclusions of the study show that the incorporation of digital competencies in the pedagogical practice not only enriches learning, but also promotes a dynamic, inclusive environment adapted to the demands of the digital era. This research work not only contributes to the academic knowledge on basic education, but also highlights the importance of having adequate technological resources to facilitate this integration, as well as offering valuable processes and recommendations for the continuous improvement of teaching practice in a constantly evolving educational context.